CRACKING THE CODE: AN EMPIRICAL EXPLORATION OF SOCIAL LEARNING THEORY AND COMPUTER CRIME. - Morris, Robert G.; Blackburn, Ashley G. (Journal of Crime & Justice, 2009)
Computer crime and related behaviors have received increased attention in recent years, yet there is still a paucity of research focusing on the behaviors surrounding computer hacking In the present study, we extend Akers' social learning theory (SLT) to explore the etiology of four forms of computer hacking (guessing passwords, attempted hacking, malicious file manipulation, and using/creating computer malware), thus filling a gap in the literature. Based on self-report data (n=600), our findings lend modest support to SLT, however the impact of social learning components may vary across different types of computer hacking Limitations are discussed and suggestions for future research are provided.